Conceptualization of Intuitive Planning in Commercial Services - Elzbieta SKAPSKA (Communications of International Proceedings, 2020)
Contemporary conditions on a service market require dynamic planning to create new quality and value in products and services. The use of an intuitive planning concept may prove to be an effective tool. The aim of the study was to fill a gap in research on the subject of services in a theoretical way as well as in a reviewing and cognitive framework. In order to reach the goal, creative and empirical research has been performed in which the most important role is played by intuitive reasoning that is supported by rational reasoning. For the purposes of the article, several distinct components of the process of providing market services were analyzed and conceptualized on the basis of perception and intuition that are at the heart of this sort of planning. The following research questions were formulated: can intuitive planning be applied to service-oriented business activity and does its introduction make sense in the process of service provision? Are there visible differences in production planning and service provision processes? The result of scientific deliberations constitutes a set of recommendations for service providers with regard to planning service-oriented activities in economic practice in the context of their profitability and aptitude for bringing prosperity. Based on the trial of 247 students, the results have shown that the most indications are assigned to the ‘forecast of the optimal achievement of a goal’ and the fewest – ‘taking risks, but with the chance of significant rewards’.
Keywords: planning; intuition; rationality; commercial services; service provision process.